Successful Retrieval of Fish Hook From Indian Flap-Shelled Turtle (Lissemys punctata) via Intra-oral Approach - Gautam, Deepesh; Singh, Deepa; Kumar, Adesh; Patra, Sarit Kumar; Ahirwar, Manoj Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Lissemys punctata, an Indian flap-shelled turtle is a fresh water species found widespread and common in South  Asia. Injuries due to entangled fish hook is the most common  affection reported in these species (Balazs and Poley, 1993). Because fresh water turtles are opportunistic scavengers and  also take live prey, they are most likely vulnerable to capture  with baited hooks set to catch fish (Howey and Dinkelacker,  2013). The present case report discusses the retrieval and  management of an entangled fish hook in an  Indian flap shelled turtle.
Keywords: Successful Retrieval; Fish Hook From; Lissemys punctata